2019
DOI: 10.1080/10872981.2019.1583969
|View full text |Cite
|
Sign up to set email alerts
|

A near-peer regional surgical teaching programme designed by medical students, delivered by junior doctors

Abstract: Background: Near-peer teaching initiatives has been shown to be a highly successful method of improving student learning. There has been little data on surgical teaching initiatives of this kind and little data to show if this improves student confidence in surgical topics. This study was designed to show whether a regional surgical teaching programme, delivered by junior doctors, improves confidence levels of students prior to their final examinations. Method: Final year medical students were invited from fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…To achieve the highest possible educational success, it is important to involve all participants in the teaching process [ 16 , 23 ]. Therefore, the implementation of online learning due to COVID-19 was evaluated using a Likert scale, the standard procedure for surveys in the field of medicine [ 17 , 19 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the highest possible educational success, it is important to involve all participants in the teaching process [ 16 , 23 ]. Therefore, the implementation of online learning due to COVID-19 was evaluated using a Likert scale, the standard procedure for surveys in the field of medicine [ 17 , 19 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Margaryan et al described the high relevance of involving students in teaching and respecting their preferences of teaching methods to achieve the highest possible educational success [24]. Therefore, the training modules of the present study were evaluated using a Likert scale, which is a standard procedure for surveys in the field of medicine [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The undergraduate medical curriculum does not regularly dedicate time to the teaching of educational theory and delivery. 39 40 A precourse orientation workshop was organised to tackle this problem. Gottlieb et al found that creating a formal teaching workshop prior to the commencement of a teaching course reduces the issues surrounding the preparation of teaching sessions.…”
Section: Discussionmentioning
confidence: 99%
“…42 With the varying amount of questions used in other NPT programme tests, a further validated tool is required to determine the number of questions required in each test to provide a perfect balance between not detracting from valuable session time while also giving a true assessment of students’ knowledge. 40 43 44…”
Section: Discussionmentioning
confidence: 99%